ABOUT OPTIMAL DATES OF SATELLITE IMAGES ACQUISITION FOR ARABLE SOIL MAPPING - I. Yu. Savin; E. Yu. Prudnikova (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
The state of the exposed surface of arable soils strongly varies in time and depends on properties of the upper soil horizon, meteorological conditions, and specific character of its usage. A change of the arable soil surface has a significant effect on their image on remote sensing data. For the maximum extraction of information about the spatial heterogeneities of soil properties satellite survey must be carried out before the first treatment of the surface of arable soils in spring.